Looking for Dante: exploring the 'Divine Comedy' in print from the 15th century to today - Ho, W-G; Bowen, R; Gilson, S (Taylor Institution Library, 2024)
When we pick up a book, we might forget that as well as reading a text we are looking at a physical object. This is not the case for the medieval poet Dante, whose famous poem, the ‘Divine Comedy’, was made into beautiful objects in the form of early printed books. The oldest of these books date back to the very beginning of the print revolution, over 550 years ago.